Dynamic measurements to assess stress levels on buried hydraulic structures - A. M. Anwar; A. S. Hashad; M. Omar (Water Science)
Old masonry structures have a very special nature that require periodical inspection and evaluation programs. The problem becomes more sophisticated when dealing with vital buried hydraulic structures under continuous functional operation while bearing additional loads from running public services such as railways. This could add extra challenges for determining their structural performance and engineering characteristics if conventional methods are used. Moreover, traditional methods are sometimes costly, time consuming, and can lead to some damage to the structure. The importance of the current research is therefore providing a rapid methodology for evaluating these structures to confirm their current ability to resist operating loads safely, especially when subjected to aging. In this study, the evaluation depends mainly on analyzing the vibration acceleration response of a structure under dynamic loads. Insight into system identification using formal modal analysis was also conducted. Simultaneously, calibrated numerical model was then adopted to predict the expected level of internal stresses. An old masonry irrigation intake buried culvert underneath the main railway lines was selected for examination. The structure was firstly plugged from both sides and emptied, site inspection as well as core sampling of construction materials were conducted. Vibration time history was recorded due to train passage with different speeds. The filed measurements along with mathematical model were used to estimate the level of stresses among the structure. The results showed the ability of the proposed method to evaluate structures in an easy and rapid fashion compared to traditional methods without stopping serviceability of the structure.